Pengaruh User Generated Content terhadap Niat Pembelian oleh Konsumen Melalui Channel GadgetIn - Yoga Adi Wijaya; Erlita Ridanasti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of perceived credibility, information quality, brand involvement, and trust on purchase intentions with attitudes towards UGC as a mediating variable. Using a quantitative approach, questionnaires were distributed to 150 YouTube application users in Indonesia who knew the GadgetIn channel and were interested in buying a smartphone. Data analysis was carried out with PLS-SEM using SmartPLS 4.1.0.6 software. The findings show that information quality and trustworthiness have a positive and significant influence on attitudes towards UGC, while perceived credibility and brand engagement do not show a significant influence. In addition, attitudes towards UGC have a positive and significant effect on purchase intentions.